Combination of SMART and CRITIC Methods in Decision Support Systems for Determination of Superior Products - Gunawan, Rakhmat Dedi (Journal of Information Technology, Software Engineering and Computer Science (ITSECS), 2024)
Superior products are goods or services that have a higher value compared to other similar products because of their quality, innovation, or uniqueness. These products are usually produced through a standardized production process, utilizing selected raw materials, and supported by modern technology and special skills. The determination of superior products is carried out through a comprehensive analysis process to identify goods or services that have great potential to provide added value, both economically and socially. The main problem in determining superior products often arises due to the lack of accurate and comprehensive data on market potential, product quality, and consumer needs. Inaccuracies in setting evaluation criteria or weights given to each criterion can also result in bias in the selection process. This research aims to implement a combination of SMART and CRITIC methods in a decision support system to determine superior products objectively and efficiently. This combination is designed to take advantage of the advantages of the SMART method in evaluating alternatives based on multi-criteria utility, as well as the CRITIC method in determining the weight of the criteria objectively based on data variation and correlation between criteria. The results of the ranking of seven products are based on the total value that has been calculated using a certain evaluation method. Product G (D700) ranks first with the highest score of 0.78961, showing the best performance compared to other alternatives. These results provide clear information about which products are superior and can be the basis for decision-making in choosing the best product.